Implementation of Project-Based Learning to Enhance the Language Skills of Students at Universitas Sindang Kasih Majalengka - Endah Meilani Sari (CV. Intake Pustaka, 2025)
Speaking skills are a fundamental aspect of Indonesian language education, serving not only as a medium for conveying ideas but also as a crucial tool for academic achievement and professional readiness; however, many students still face challenges such as low confidence, communication anxiety, and limited opportunities for authentic practice, which hinder the optimal development of their oral proficiency. To address this issue, the present study explores the implementation of Project-Based Learning (PjBL) as an innovative pedagogical strategy to enhance the speaking skills of students in the Indonesian Language Education Program at Universitas Sindang Kasih Majalengka. Employing a qualitative approach with purposive sampling, this research focused on fourth-semester students actively involved in project activities, with data gathered through in-depth interviews, participatory observation, and document analysis, which were subsequently examined using thematic analysis to identify patterns and generate insights. The findings demonstrate that PjBL significantly improves students’ speaking skills by providing contextualized opportunities for repeated oral practice through project presentations, group discussions, and authentic communication tasks, thereby strengthening phonology, diction, fluency, and rhetorical ability while simultaneously fostering self-confidence and active participation. Furthermore, the relevance of projects to real-life contexts intrinsically motivated students, encouraged them to think critically and creatively, and supported the development of collaborative learning attitudes. Continuous feedback from lecturers and peers also facilitated reflection and refinement, allowing students to gradually enhance their communicative competence.